Characterization of plasma-induced cell membrane permeabilization: focus on OH radical distribution. (21st July 2016) - Sasaki, Shota; Honda, Ryosuke; Hokari, Yutaro; Takashima, Keisuke; Kanzaki, Makoto; Kaneko, Toshiro
Abstract: Non-equilibrium atmospheric-pressure plasma (APP) is used medically for plasma-induced cell permeabilization. However, how plasma irradiation specifically triggers permeabilization remains unclear. In an attempt to identify the dominant factor( s ), the distribution of plasma-produced reactive species was investigated, primarily focusing on OH radicals. A stronger plasma discharge, which produced more OH radicals in the gas phase, also produced more OH radicals in the liquid phase (OHaq ), enhancing the cell membrane permeability. In addition, plasma irradiation-induced enhancement of cell membrane permeability decreased markedly with increased solution thickness (<1 mm), and the plasma-produced OHaq decayed in solution (diffusion length on the order of several hundred micrometers). Furthermore, the horizontally center-localized distribution of OHaq corresponded with the distribution of the permeabilized cells by plasma irradiation, while the overall plasma-produced oxidizing species in solution (detected by iodine-starch reaction) exhibited a doughnut-shaped horizontal distribution. These results suggest that OHaq, among the plasma-produced oxidizing species, represents the dominant factor in plasma-induced cell permeabilization. These results enhance the current understanding of the mechanism of APP as a cell-permeabilization tool.